2004
DOI: 10.1111/j.1365-2958.2004.04292.x
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic phenotypes and translocated effector proteins of the Mesorhizobium loti strain R7A VirB/D4 type IV secretion system

Abstract: SummaryThe symbiosis island of Mesorhizobium loti strain R7A contains genes with strong similarity to the structural vir genes ( virB1-11 ; virD4 ) of Agrobacterium tumefaciens that encode the type IV secretion system (T4SS) required for T-DNA transfer to plants. In contrast, M. loti strain MAFF303099 lacks these genes but contains genes not present in strain R7A that encode a type III secretion system (T3SS). Here we show by hybridization analysis that most M. loti strains contain the VirB/D4 T4SS and not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 53 publications
(119 reference statements)
2
171
0
Order By: Relevance
“…Two other secretion systems are common to plant-associated bacteria, type III and IV secretion systems, which transport a wide variety of effector proteins into the extracellular medium or into the cytoplasm of eukaryotic host cells and affect interaction [26][27][28][29] . Intriguingly, neither system is present in strain BH72, probably preventing the export of toxic proteins to the host.…”
Section: Plant-associated Lifestylementioning
confidence: 99%
“…Two other secretion systems are common to plant-associated bacteria, type III and IV secretion systems, which transport a wide variety of effector proteins into the extracellular medium or into the cytoplasm of eukaryotic host cells and affect interaction [26][27][28][29] . Intriguingly, neither system is present in strain BH72, probably preventing the export of toxic proteins to the host.…”
Section: Plant-associated Lifestylementioning
confidence: 99%
“…Rhizobia were shown to use T3SS to promote or impair symbiosis upon secretion of type three effectors that often have homologs in pathogenic bacteria (Deakin and Broughton, 2009). Known negative effects of rhizobial T3SS include alteration of root hair infection and nodule formation (Chatterjee et al, 1990), nodule infection (Hubber et al, 2004) or symbiosome differentiation (Yang et al, 2010). Thanks to the dual regulation of HrpG, our work showed that T3SS can block both root hair and intracellular infection on the same host plant.…”
Section: Discussionmentioning
confidence: 88%
“…We could not, however, detect transfer of a Cre fusion with the C-terminal 10 aa to the kanamycin reporter line (see below for transfer by using a more sensitive GFP reporter line). Importantly, there was no transfer of Cre::VirF19C from virD4 mutant LBA2587 (27), showing that translocation mediated by this short sequence also still depends on the presence of an intact T4SS.…”
Section: Resultsmentioning
confidence: 99%
“…Selection conditions of the strains and methods for introduction of plasmids are described in detail elsewhere (26). In some experiments, LBA2587, a derivative of LBA1100 with a precise deletion of virD4 (27), was used.…”
Section: Methodsmentioning
confidence: 99%